simplify completely: (3a^3b )-3

--------------
( 2a^-1b^2)

1 answer

I am assuming the numerator is to the power of -3

numerator becomes 1/3 * a^0 * 1/b^3= 1/3b

denominator is 2b^2/a

putting it together

numerator * 1/denominator

1/3b * a/2b^2= a/6b^3
Similar Questions
  1. Consider the following functions.f(x) = x2 − 3x, g(x) =√(x+2) (a) Find (f *g)(x). (Simplify your answer completely.) (B)Find
    1. answers icon 1 answer
  2. Factor f(x) into linear factors given that k is a zero of f(x).f(x)=x^3+(12-4i)x^2+(32-48i)x-128i, k=4i In completely factored
    1. answers icon 2 answers
  3. Factor f(x) into linear factors given that k is a zero of f(x).f(x)=x^3+(12-4i)x^2+(32-48i)x-128i, k=4i In completely factored
    1. answers icon 1 answer
    1. answers icon 2 answers
more similar questions